ISMR 2020 proceedings of the 7th International Symposium on Innovation and Sustainability of Modern Railway - Lei, Xiaoyan (IOS Press, 2020)
Intro -- Title Page -- Preface -- Contents -- Railway &amp -- Mechanics -- Geosynthetic Encased Columns Supporting Rail Infrastructure - Perspectives on Research and Case Studies -- Application Research of TMD on Low Frequency Vibration Control of Track Box Girder Structure -- The Influence Evaluation of the Waste Slag Above Tunnel on the Safety of the Structure of the High-Speed Railway Tunnel -- Experimental Study on Mechanical Properties of Concrete in the Complex Environment of China-Laos (Moding-Vientiane) Railway -- Influence of Shield Tunnel and Train Load on Existing Bridge Piles -- Analysis of the Influence of Track Lateral Irregularity on the Stability of Seamless Turnout -- Early Hardening Process of CA Mortar Indicated by Electrical Resistivity -- Numerical Study on Noise Reduction of High-Speed Train Based on Non-Smooth Surface -- Study on Rail Short-Wave Irregularity of Speed Increased Tracks -- Study on the Influence of the Marshalling Position of Vehicles Without Braking Function on the Safety of Empty Freight Trains Under Braking Condition -- Study on Radial Stiffness of Contact Pair of Logarithmic Modified Tapered Roller Bearing -- Experimental Study on Characteristics of Short Wave Irregularity in Urban Rail Transit -- Railway &amp -- Computer Science -- Metal Effect on Reliability of Balise Transmission System Antennas -- Energy Saving Optimization of High Speed Train Based on Speed Prediction Control Curve -- Severity Analysis of Debris Flow Hazards in Chengkang Railway Based on G1-ANP and Improved Radar Chart -- Image Filtering Algorithm of Subway Tunnel Cracks Based on Regional Difference -- C3+ATO Function Simulation and Verification Analysis Based on Timed Automata -- Estimation of Dynamic Response Index Domain of High Speed Railway Vehicle System.
Open access
Keywords: Railroad engineering--Congresses; Railroads--Data processing--Congresses; Railroads--Management--Congresses; Electronic books; Konferenzschrift